Beyond the Allegory: The Grotesque Body and the Limits of Liberation in Marlene Van Niekerk's Agaat. Issue 2 (2nd July 2016) - Pretorius, Antoinette
Abstract : Agaat by Marlene van Niekerk (translated into English by Michiel Heyns) details the subjectivity of its bed-ridden and paralysed protagonist, Milla Redelinghuys, as well as the complex relationship she shares with her caregiver, Agaat. Through reading Milla's body in relation to Mikhail Bakhtin's notion of the grotesque, this article aims to explore the ways in which the text problematizes overly allegorical readings of the novel that emphasize Milla's death as leading to Agaat experiencing rebirth. This is achieved through focusing on the ways in which Van Niekerk undermines the sense of social transcendence that Bakhtin considers indispensable to the carnival. In order to do this, I examine two instances that most closely align Milla's corporeality with Bakhtin's idea of the grotesque: the scene in which Milla pretends to be dying in order to play a joke on her neighbour is read in relation to the idea of 'carnival laughter', and the scene in which she wakes up to discover Agaat sleeping on her bed is analysed through Bakhtin's description of the 'two-bodied image'. I conclude that these gestures towards an association with the grotesque form part of the larger project of incompletion that Van Niekerk stages in the novel.